Combinatorial analysis of marine based biomaterials: high-throughput analysis of the effect of nanostructured multilayers on cell behaviour - Neto, Ana I. (2013)
Publicado em "Journal of Tissue Engineering and Regenerative Medicine", vol. 7, supp. 1 (2013)